Rwanda Social Accounting Matrix (SAM), 2011 - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The 2011 Social Accounting Matrix for Rwanda is based on newly estimated supply-use tables, national accounts, state budgets, and balance of payments. The SAM reconciles these data using cross-entropy estimation techniques. The final SAM is a detailed representation of Rwanda's economy. It separates 54 activities and commodities; labor by different sectoral types; and households by rural/urban areas as well expenditure quintiles. Labor and household information is drawn from the most recent Rwanda Living Expenditure Survey. Finally, the SAM identifies government, investment and foreign accounts. It is therefore an ideal tool for economywide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.